Impact of Digital Marketing Strategy on Consumer Purchasing Decisions: Case Study in the Retail Industry in Bandung City - Rafikah, Syarifah (Journal of Management, 2023)
This study aims to analyze the impact of digital marketing strategies on consumer purchasing decisions in the retail industry in Bandung City. Using a survey method, data was collected from 100 respondents consisting of various demographic groups. Descriptive analysis shows that social media, email marketing, search engine optimization (SEO), and paid advertising have a significant role in influencing consumer purchasing decisions. The results show that the majority of respondents use social media daily, with Facebook and Instagram as the most dominant platforms. Email marketing also proved effective, although response rates still need to be improved. SEO plays an important role with many respondents relying on product reviews and reviews as the main source of information. Paid advertising is considered to be quite influential in purchasing decisions.The frequency of online purchases shows that most respondents make purchases once every 2-3 months, with price and product quality as the main factors that influence their decisions. Based on these findings, it is recommended that retail companies in Bandung City improve their digital marketing strategies by focusing on engaging content on social media, personalization in email marketing, SEO optimization, and effective use of paid advertising. This research provides important insights for business practitioners and marketers on how digital marketing strategies can be optimized to increase conversions and influence consumer purchasing decisions in the digital age.